Distribution and Environmental Impact Factors of Picophytoplankton in the Eastern Indian Ocean - Xingzhou Wang; Feng Wang; Jun Sun (Journal of Marine Science and Engineering, 2022)
Picophytoplankton (pico) in the eastern Indian Ocean (EIO) were investigated during the inter-monsoon periods. They were found to typically comprise Prochlorococcus (Pro), Synechococcus (Syn), and Picoeukaryotes (PEuks). In the survey area, the pico showed two different vertical distribution patterns in different regions, whereby the Syn abundance decreased with depth, whereas those of Pro and PEuks increased and then decreased with depth, with the maximum depths ranging from 50 to 100 m. The cell abundance and community structure of the pico were similar at the equator (EQ) and the eastern boundary of the Indian Ocean near Sumatra (EB), but the pico cell abundance was significantly lower in the Bay of Bengal (BOB). Pro dominated most regions of the entire EIO and were approximately one-to-two orders of magnitude more abundant than Syn and PEuks. The distributions of Syn and PEuks showed little difference across various regions. Influenced by the physicochemistry of circulation and water masses, there were many different environmental factors in the different regions. The abundance of pico domination by Pro showed a strong positive correlation with the nutrients and salinity in the survey area, indicating increasing nutrient availability, particularly in the oligotrophic EIO. Generalized additive models (GAMs) analysis showed the differences in their responses to environmental variability. Pro and PEuks both increased strongly with warming up to below 26 °C, and Pro and PEuks were more responsive to chemical (nutrient) variability. Syn showed a broader tolerance of low-salinity conditions. In a certain range, an increase in nitrite and nitric acid can improve the cell abundance of Pro. As a significant contributor to primary productivity in oligotrophic waters, this study provides essential information for studying pico communities in the EIO and its adjacent marine ecosystems.